PENGARUH TINGKAT RETURN DAN RISK TERHADAP KEPUTUSAN BERINVESTASI DIREKSADANA SYARIAH - Syafa’ah, Nurul Laily (Fakultas Ekonomi dan Bisnis Islam, 2020)
The purpose of this study was to determine the effect of the level of return and risk on investment decisions of Islamic directors in Islamic Economics and Business Faculty students at IAIN Kudus. The design of this study is quantitative. The population in this study were all students of the Faculty of Economics and Islamic Business IAIN Kudus. The sample of this study was 100 respondents who were selected using a non random sampling technique with a purposive sampling type with a sample of students who had received a course on mutual funds. Data collection through questionnaires distributed online with the Google form link. The instrument trials were analyzed using validity and reliability tests. The technique of multiple linear regression analysis and hypothesis testing. The data is processed and analyzed using SPSS application for Windows version 22. The results of this study indicate that the Return and Risk variables partially have a positive effect on investment decisions in Syariah Funds, simultaneously the Return and Risk variables have a significant effect on investment decisions in sharia mutual funds.